Industry learning environments and the heterogeneity of firm performance - Balasubramanian, Natarajan; Lieberman, Marvin B. (Strategic Management Journal, 2009)
This paper characterizes interindustry heterogeneity in rates of learning‐by‐doing, and examines how industry learning rates are connected with firm performance. Using plant‐level data from the U.S. manufacturing sector, we measure the industry learning rate as the coefficient on cumulative output in a production function. We find that learning rates vary considerably among industries and are higher in industries with greater R&D, advertising, and capital intensity. More importantly, we find that higher rates of learning are associated with wider dispersion of Tobin's q and profitability among firms in the industry. These findings suggest that learning intensity represents an important characteristic of the industry environment that affects the range of firm performance. Copyright © 2009 John Wiley & Sons, Ltd.